Favorable longterm outcomes of liver transplant recipients treated de novo with once‐daily tacrolimus: Results of a single‐center cohort. Issue 10 (October 2016) - Gastaca, Mikel; Valdivieso, Andrés; Bustamante, Javier; Fernández, José R.; Ruiz, Patricia; Ventoso, Alberto; Testillano, Milagros; Palomares, Ibone; Salvador, Patricia; Prieto, Mikel; Montejo, Miguel; Suárez, María J.; et al.
Abstract : The once‐daily prolonged‐release formulation of tacrolimus has been recently related with significant graft and patient mid‐term survival advantages; however, practical information on the de novo administration after liver transplantation and longterm outcomes is currently lacking. This study is a 5‐year retrospective analysis of a single‐center cohort of liver transplant recipients treated de novo with once‐daily tacrolimus (April 2008/August 2011). The study cohort consisted of 160 patients, including 23 with pretransplant renal dysfunction, with a median follow‐up of 57.6 months (interquartile range, 46.6‐69.0). Tacrolimus target trough levels were 5‐10 ng/mL during the first 3 months after transplant, reducing progressively to <7 ng/mL after the first posttransplant year. Once‐daily tacrolimus was withdrawn in 35 (21.8%) patients during follow‐up, mostly due to renal dysfunction and/or metabolic syndrome. The biopsy‐proven acute rejection rate was 12.5% with no cases of steroid‐resistant rejection. The cumulative incidence of de novo diabetes, hypertension, and dyslipidemia were 16.9%, 31.2%, and 6.5%, respectively. Hepatocellular carcinoma recurrence rate was 2.8%. Renal function remained stable after the sixth month after transplant with a mean estimated glomerular filtration rate of 77.7 ± 19.6 mL/minute/1.73 m 2 at 5 years. None of our patients developed chronic kidney disease stage 4 or 5. Patient survival at 1, 3, and 5 years was 96.3%, 91.9%, and 88.3%, respectively. Overall survival of patients with Model for End‐Stage Liver Disease (MELD) score > 25 points was not significantly different. In conclusion, our study suggests that immunosuppression based on de novo once‐daily tacrolimus is feasible in routine clinical practice, showing favorable outcomes and outstanding longterm survival even in patients with high MELD scores. Liver Transplantation 22 1391–1400 2016 AASLD .